Integration of ROBO-analyzer for forward and inverse kine-mastics of 6 DOF robot to check flexible DH parameters. - Yenurkar, Nayan; Giri, Jayant; Chadge, Rajkumar (International Journal of Engineering and Technology, 2018)
The installation of the robotic arm is based on the type of application to be carried out. On the basis of the application, the task performs by the industrial robotic arm is the command of inputs provided by the operator. The changes in the design of industrial robotic arm are associated with the changes in the parameters such as required work volume, payload capacity, link length, type of joint, degree of free- dom. The need for industries to carry out efficient work focuses on the features of the robotic arm. The main feature associated with a robotic arm is its flexibility. This paper proposes a methodology to obtain flexibility in robotic arm and its impact on the DH parameters along with velocity, acceleration, forces associated with the joint. To solve the inverse kinematics of complex robotic arm the integration is done with RoboAnalyzer software.Â Â